CBP-induced stimulation of c-Fos activity is abrogated by E1A. - Bannister, A J (1995)
The CBP protein stimulates transcription of cAMP-responsive genes by binding to the phosphorylated activation domain of the CREB transcription factor. Here we show that CBP stimulates transcription of Fos/Jun activity in F9 cells and that this response of mediated, at least partly, via c-Fos. We show that CBP binds c-Fos in a phosphorylation-independent manner in vitro, using a domain distinct from that required to bind CREB. When this CBP domain is linked to the activation domain of VP16 it can stimulate GAL4-Fos activity in vivo. The domain of CBP that binds c-Fos is also used to contact the E1A protein. We therefore asked whether the documented repression of AP1 activity by E1A is due to sequestration of CBP from c-Fos. We show that E1A 12S can repress c-Fos activation functions. The use of E1A mutants indicates that binding of CBP, but not RB, to E1A is essential for E1A-mediated repression. These data support a model whereby E1A can modulate AP1 activity by directly competing for the CBP co-activator protein.